Pertanggungjawaban Hukum Pelaku UMKM atas Kecelakaan Kerja Akibat Kelalaian K3 di Kota Cirebon - Asilah Nur Azizah; Diky Dikrurahman (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the regulation and implementation of Occupational Safety and Health (OSH) as well as the legal liability of MSME owners for workplace accidents resulting from OSH negligence at Haji Ola Tofu Factory in Cirebon City. This research employed an empirical juridical method through literature review and interviews. The findings reveal that the employer has provided personal protective equipment; however, OSH implementation remains inadequate due to low worker compliance and weak supervision, leading to workplace accidents. The employer’s liability is limited to covering medical expenses, while the workers have not been registered with BPJS Ketenagakerjaan. This condition indicates that the employer has not fully complied with legal obligations regarding worker protection as mandated by Indonesian labor laws.